Three-Tesla magnetic resonance imaging of the vestibular endolymphatic space: A systematic qualitative description in healthy ears. Issue 109 (December 2018) - Conte, Giorgio; Caschera, Luca; Tuscano, Bruno; Piergallini, Lorenzo; Barozzi, Stefania; Di Berardino, Federica; Zanetti, Diego; Scuffi, Chiara; Scola, Elisa; Sina, Clara; Triulzi, Fabio
Abstract: Background and Purpose: A detailed knowledge of the normal Magnetic Resonance (MR) anatomy of the vestibular endolymphatic space (ES) could be useful to understand the linkage between endolymphatic hydrops (EH) and Ménière's disease (MD). Our aim was to describe the MR anatomy of the vestibular ES as depicted by MR imaging in healthy ears. Methods: This report describes a single-center retrospective study. Three readers analyzed the healthy ears of 22 consecutive patients who had undergone MRI for unilateral sudden hearing loss. The readers described the vestibular ES based on a delayed post-contrast 3D-FLAIR sequence according to six well-defined planes, three oblique sagittal (lateral, intermediate and medial) planes and three axial (superior, intermediate and inferior) planes. Results: On sagittal lateral and intermediate planes, we identified the SSC ampulla combined with the utricle in 22/22 ears. On the sagittal medial plane, the saccule was detectable in 15/22 (68%) ears, having a club shape with the long axis oriented cranio-caudally; in 7/22 (32%) ears, the saccule presented an oval/round shape that appeared more conspicuously on the axial intermediate plane. The ES occupied the half superior portion of the vestibule in 22/22 ears, never contacting the round and oval windows. On the axial plane, in 17/22 cases, the ES showed a Y-shaped arrangement, while in 5/22 ears (23%), the ES presented a more globular shape. Conclusion: MR imaging represents a valid tool to explore the in vivo anatomy of the vestibular ES and to highlight its variability in normal ears.